Analisis Pengaruh Dimensi Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Pasien Di RSUD Tongas Kabupaten Probolinggo - Yullyta Widiastuti; H.M. Saiful Bahri; Hermanto (STIE Mandala Jember, 2020)
The satisfaction felt by the patient is an indicator of the quality of service in a hospital. The quality of services provided to patients will be compared between expectations and perceived reality so that they arise feeling satisfied or dissatisfied. One important factor in the effort to create satisfaction is to provide good quality service. Quality hospital services means not only felt by patients but also felt by their families, so that patients feel satisfaction and will ultimately be able to increase the confidence of both patients and the patient's family to the hospital.Based on the results of the analysis of influence, both collectively and separately, the dimensions of quality and trust in satisfaction indicate the value of the coefficient Fcount is greater than the value of F table with a significance level smaller than alpha 0.05, indicating that the dimensions of service quality and trust together affect satisfaction patients, while the calculated t coefficient value of each independent variable shows a coefficient that is greater than the value of the t table coefficient with a significance of less than alpha0.05, this means that trust and quality dimensions affect patient satisfaction in Tongas Hospital Probolinggo. Based on the t value of each independent variable shows that direct evidence which has a dominant influence on patient satisfaction. Keywords:Quality Dimensions, Patient Trust and Satisfaction